White Supremacy on CNN and Fox: AC 360 and Hannity Coverage of the Charlottesville 'Unite the Right' Rally. (28th May 2023) - el-Nawawy, Mohammed; Hamas Elmasry, Mohamad
ABSTRACT: This research examines CNN and Fox News coverage of the 2017 "Unite the Right" rallies held in Charlottesville, VA. The study uses critical race theory to examine how Fox News 's Hannity and CNN' s AC 360 talk about race and racism in American society in the context of a polarizing, racially-charged event. Results from the textual analysis suggest that both programs structured their coverage around President Donald Trump's reaction to the rally. Hannity 's content was primarily structured around themes of defense and blame — it defended Trump and Republicans and cast blame upon Democrats, liberal activists, Black people, and mainstream media. AC 360 constructed Trump as a racist and "unfit" to be president, but also presented a conflicted discourse about racism in American society. Specifically, some of the show's guests suggested that American society had largely moved past extreme forms of racism. Other guests, however, implied that some Americans have exaggerated the extent to which American society has moved beyond racism. Both shows offered up at least some support for the idea that America has become a "post-racist" society.